Design and Implementation of a MongoDB-Based Digital ‎Archiving System for Government Office Record: A Case Study ‎of Kelekar District Office‎ - Abiyyu Muhamad Fadholi; Alek Wijaya; M. Soekarno Putra; Siti Sauda; Dwi Ammelia Galuh‎ Primasari (JPI: Jurnal Pustaka Indonesia, 2026)
The Kelekar District Office faces the inefficiency of manual archive management and the limitations of relational databases in handling dynamic document metadata variations. This research aims to design and build digital archiving software based on a Non-Relational Database (NoSQL) to overcome the rigidity of conventional data storage structures. The system development method uses a Prototyping model, which includes communication, rapid planning, design modeling, prototype construction, and user delivery. The system is built using the Laravel framework integrated with MongoDB as a JSON/BSON-based document storage medium. The result of this research is a digital archive application design that implements a schema-less concept, which is expected to accommodate the storage of various types of documents with different attributes in a single, flexible collection and improve the efficiency of searching unstructured archive data compared to previous methods.